Layering PLGA-based electrospun membranes and cell sheets for engineering cartilage-bone transition - Ye, H; Mouthuy, P; El-sherbini, Y; Cui, Z (John Wiley and Sons, Ltd., 2013)
It is now widely acknowledged that implants that have been designed with an effort towards reconstructing the transition between tissues might improve their functionality and integration in vivo. This paper contributes to the development of improved treatment for articular cartilage repair by exploring the potential of the combination of electrospinning technology and cell sheet engineering to create cartilage tissue. Poly(lactic-co-glycolic acid) (PLGA) was used to create the electrospun membranes. The focus being on the cartilage-bone transition, collagen type I and hydroxyapatite (HA) were also added to the scaffolds to increase the histological biocompatibility. Human mesenchymal stem cells (hMSCs) were cultured in thermoresponsive dishes to allow non-enzymatic removal of an intact cell layer after reaching confluence. The tissue constructs were created by layering electrospun membranes with sheets of hMSCs and were cultured under chondrogenic conditions for up to 21 days. High viability was found to be maintained in the multilayered construct. Under chondrogenic conditions, reverse-transcription-polymerase chain reaction (RT-PCR) and immunohistochemistry have shown high expression levels of collagen type X, a form of collagen typically found in the calcified zone of articular cartilage, suggesting an induction of chondrocyte hypertrophy in the PLGA-based scaffolds. To conclude, this paper suggests that layering electrospun scaffolds and cell sheets is an efficient approach for the engineering of tissue transitions, and in particular the cartilage-bone transition. The use of PLGA-based scaffold might be particularly useful for the bone-cartilage reconstruction, since the differentiated tissue constructs seem to show characteristics of calcified cartilage. Copyright © 2013 John Wiley and Sons, Ltd.